Aspectos clínicos influentes no planejamento das próteses sobre implantes tipo overdenture e protocolo - Torcato, Leonardo Bueno [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Goiato, Marcelo Coelho [UNESP]; Falcón-Antenucci, Rosse Mary [UNESP] (My University, 2012)
The aim of his study was to review the current scientific literature in order to discuss the surgical, prosthetics and psychological/psychosocial aspects during the treatment planning of edentulous patients, when a total fixed prosthesis or overdenture is indicated. To identify studies to take part in this review, a search was conducted for the following databases: PubMed, Dentistry and Oral Sciences Source, Journals@Ovid, SpringerLink, Wiley Online Library, Nature (NPG), Oxford Journals. It was used as descriptors: total fixed prostheses and overdentures. Inclusion criteria were: clinical articles, clinical case reports, case series, literature reviews and systematic reviews that addressed the study and comparison of total fixed prostheses and overdentures for a surgical- prosthetic planning. Exclusion criteria were: laboratory and in vitro studies and those whose first language was not English or Portuguese. Of a total of 454 articles, after an analysis according to inclusion and exclusion criteria, 76 articles were selected. During an implantsupported prosthesis rehabilitation with dental in edentulous patients, the use of alternative procedures appear to be effective when compared to more invasive surgical techniques, and thus, the amount of dental implants possible to install associated with prosthetic issues such as lip support, smile line, quantity and quality of mucosa, phonetics, etc., will allow an appropriate treatment planning to each clinical case

O objetivo do presente estudo foi realizar uma revisão da literatura científica atual, a fim de discutir os aspectos cirúrgicos, protéticos e psicológicos/psicossociais durante o planejamento reverso de pacientes edêntulos, frente à utilização de próteses tipo protocolo e overdenture. Para a identificação dos estudos da revisão, foi realizada uma busca para os seguintes bancos de dados: PubMed, Dentistry and Oral Sciences Source, Journals@Ovid, SpringerLink, Wiley Online Library, Nature (NPG), Oxford Journals. Foram utilizados como descritores: overdenture e total fixed prostheses. Os critérios de inclusão foram: artigos clínicos, relato de casos clínicos, casos seriados, revisões de literatura e revisões sistemáticas que abordaram o estudo e a comparação das próteses tipo protocolo e overdenture durante o planejamento cirúrgico-protético. Os critérios de exclusão foram: artigos laboratoriais, estudos in vitro e aqueles cujo idioma não foi o inglês ou o português. De um total de 454 artigos, após uma análise segundo o critério de inclusão e exclusão, foram selecionados 76 artigos. Em se tratando de uma reabilitação de próteses sobre implantes em arcos totalmente desdentados, a utilização de procedimentos alternativos parece ser eficaz, quando comparados às técnicas cirúrgicas mais invasivas e, desse modo, a quantidade de implantes dentários possíveis de serem instalados, associados a aspectos protéticos, como suporte labial, linha do sorriso, quantidade e qualidade de mucosa, fonética e etc, irão possibilitar um planejamento reverso mais adequado para cada caso.
Clinical aspects in the treatment planning of implant-supported prostheses overdenture and total fixed prostheses
Keywords: Denture design; Dental prosthesis; Implant-supported; Dental implant; Dentures; Planejamento de dentadura; Prótese dentária fixada por implante; Implante dentário; Dentaduras